Wireless ordering system for restaurants (hardware design) / Abang Sarbini Abang Ahmad - Abang Ahmad, Abang Sarbini (1995)
The main objective of this project was to design a wireless ordering system to be used in a restaurant With this remote system, time for travelling and misunderstanding of writing can be eliminated. In addition, with the aid of the personal computer, computerized management tasks like accounting, stock keeping, etc. can be integrated in this system.